Research on Adoption Behavior and Influencing Factors of Intelligent Pension Services for Elderly in Shanghai - Luo, Juan; Meng, Lingqi (Frontiers in Genetics, 2022)
With the rapid development of artificial intelligence and Internet-of-Things technology, the traditional pension service mode has changed, and intelligent pension services have become a new direction of development. Descriptive statistical analysis is conducted on the supply status and demand of intelligent pension services. It is believed that the current intelligent pension services are still in the initial stage of development, and the contradiction between supply and demand is prominent. The demand for intelligent pension of the elderly is high, but the user acceptance and satisfaction are not high. On this basis, variables were selected from individual characteristics, family situation, economic status, education level, living conditions, and other indicators for multivariate unconditional logistic regression analysis. It was found that the adoption behavior of intelligent pension service users was most significantly affected by age, number of children, living conditions, service cost, service docking channel, and equipment operation difficulty. Based on the conclusion, this article puts forward some suggestions such as taking the government as the center to realize the multi-governance of intelligent pension services, improving the supply of intelligent pension service-related facilities guided by demand, optimizing the service mode based on the platform to realize dynamic combination, and taking talents as the core to promote the high-quality development of intelligent pension services.